A switch of chaperonin function regulates the clearance of solid protein aggregates. Issue 11 (2nd November 2022) - Ma, Xinyu; Zhang, Min; Ge, Liang
ABSTRACT: Protein aggregation is related to many human diseases. Selective macroautophagy/autophagy is the major way to clear protein aggregates in eukaryotic cells. While multiple types of autophagy receptors have been reported to mediate autophagic clearance of protein condensates with liquidity, it has been unclear if and how solid aggregates could be degraded by autophagy. Our recent work identifies the chaperonin subunit CCT2 as a new type of aggrephagy receptor specifically facilitating the autophagic clearance of solid protein aggregates, and indicates that multiple aggrephagy pathways act in parallel to remove different types of protein aggregates. In addition, this work reveals a functional switch of the chaperonin system by showing that CCT2 acts both as a chaperonin component and an autophagy-receptor via complex and monomer formation.